In vitro assessment of an experimental coat applied over fluoride varnishes - Delbem, Alberto Carlos Botazzo [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Oliveira, Felipe Alberto Lino [UNESP]; Pessan, Juliano Pelin [UNESP]; Buzalaf, Marília Afonso Rabelo; Sassaki, Kikue Takebayashi [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2009)
Objective: The time of contact between the product and enamel surface is important in ensuring the efficacy of fluoride varnishes. Thus, some alternatives could avoid fluoride loss to saliva and improve the anticariogenic action of the product. This study evaluated the effect of an experimental coat on the anticariogenic action of fluoride varnishes. Material and Methods: Enamel bovine blocks were selected by evaluating surface microhardness and randomized into five groups (n=24): placebo, Duraphat™, Duraphat™ with coat, Duofluorid™ and Duofluorid™ with coat. Twelve blocks from each group were used to analyze calcium fluoride (CaF2) formed on enamel after treatment. The other 12 blocks were subjected to pH cycling for 7 days. The varnishes were kept on enamel for 6 h. Next, the percentage change of surface microhardness (%SMHC) and mineral loss (ΔZ) were calculated. CaF2 retained and fluoride present in the pH-cycled solutions were also measured. Results: The use of the coat did not decrease %SMHC and ΔZ, but all fluoride varnishes had better results when compared to the placebo (ANOVA and Kruskal-Wallis, respectively). The values from CaF2 formed were higher compared to the values of CaF2 retained (non-paired t test, p<0.05). There was a trend to decrease the amount of F in the solutions at the end of pH cycling (Kruskal-Wallis, p<0.05). Conclusions: Although the experimental coat increased the formation of CaF2 on the enamel surface, it did not significantly improve the anticariogenic action of fluoride varnishes.
Keywords: Dental caries; Prevention and Control; Topical fluorides